Case Report: Long-Term Survival of a Pediatric Patient With an Intra-Abdominal Undifferentiated Carcinoma of Unknown Primary - Stirnweiss, Anja; Dholaria, Hetal; Oommen, Joyce; Hardy, Kathy; Jevon, Gareth; Beesley, Alex H.; Kotecha, Rishi S. (Frontiers in Oncology, 2021)
An 8 year and 10 month old boy presented following two weeks of abdominal pain, vomiting, constipation, and rectal pain. A diffuse lower-abdominal mass was felt upon palpation, with radiological findings confirming the presence of a large, multilobulated intraperitoneal mass with mesenteric lymphadenopathy and hepatic metastatic disease. A biopsy of the mass revealed anatomical pathological findings consistent with a diagnosis of intra-abdominal undifferentiated carcinoma of unknown primary (CUP). The patient was treated with six cycles of carboplatin and gemcitabine prior to surgery. Following incomplete resection of the tumor, four further cycles were administered resulting in resolution of the pelvic mass, but progression in the right and left lobes of the liver. Therapy was accordingly adjusted, with administration of six cycles of ifosfamide and doxorubicin followed by one year of metronomic vinorelbine and cyclophosphamide maintenance therapy. The patient remains in remission seven years from completion of therapy. Whole exome sequencing revealed missense mutations in the DNA-repair and chromatin-remodeling genes FANCM and SMARCD2, and a tumor-derived cell line revealed a complex karyotype suggesting chromosomal instability. CUP is an extremely rare diagnosis in the pediatric population, previously reported during adolescence. This report provides detailed characterization of CUP in a young child and in the absence of defined therapeutic guidelines for pediatric CUP, the successful treatment strategy described should be considered for similar cases.